ANALISIS KEPUASAN PENGGUNAAN SIAKAD MENGGUNAKAN METODE EUCS di STIKES YAYASAN RS Dr. SOETOMO - Aisyah Hanif Azizah; Aliya Rosalita Tamazour; Nadia Rahmadani; Rito Galang Suhartanto; Dyan Angesti (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of information technology encourages higher education institutions to improve the quality of academic services by implementing the Academic Information System (SIAKAD). STIKES Yayasan RS Dr. Soetomo has adopted SIAKAD as a digital academic service facility for online academic activities such as Study Plan Cards (KRS), Study Result Cards (KHS), attendance, online guidance, temporary transcript grades, arranging class schedules, and other academic administration. However, there are still several problems such as a less than optimal interface system and delays in updating academic information. This study aims to increase the level of user satisfaction in the Academic Information System (SIAKAD) using the End User Computing Satisfaction (EUCS) method. The method used is quantitative, applying data collection techniques through questionnaire distribution to 60 active students who use SIAKAD at STIKES Yayasan RS Dr. Soetomo. The EUCS method includes 5 variables, namely content (content), accuracy (accuracy), display (format), user friendliness (ease of use), timeliness (timeless). The results of the study show that the average value for the content variable is 3.961, the accuracy variable is 3.922, the format variable is 3.972, the ease of use variable is 3.925, and the timeliness variable is 3.908. Based on these findings, the level of user satisfaction with SIAKAD at STIKES Yayasan RS Dr. Soetomo offers it is satisfactory. The findings of this study are expected to be the basis for evaluation in improving the quality of academic information system services to be more effective and in accordance with user needs.